Cardio-cerebrovascular complications in COVID-19 patients: A retrospective cohort study - Hong, Kwan; Kisiju, Trishna; Kim, Jeehyun; Chun, Byung Chul (Frontiers in Medicine, 2022)
Background: Recent studies have highlighted the cardio-cerebrovascular manifestations of coronavirus disease 2019 (COVID-19). Objective: This study aimed to analyze the likelihood of cardiovascular and cerebrovascular manifestations among patients with COVID-19-positive individuals in South Korea. Methods: A cohort database for COVID-19 from the National Health Insurance Service was used which included patients diagnosed with COVID-19 between January 1 to June 4, 2020. Individuals who tested COVID-19 positive, notwithstanding the severity of the disease, were designated as cases. COVID-19- negative individuals were used as controls for the study. The exclusion criteria included people who had a history of cardiovascular and cerebrovascular diseases between 2015 and 2019. A new diagnosis of cardiovascular and cerebrovascular complications was considered the primary endpoint. The adjusted incidence rate ratio (IRR) of development of complications was estimated using log-link Poisson regression. The model was adjusted at two levels, the first one included age and sex while the second included age, sex, residence area, and level of income. The hazard ratio was estimated using Cox-proportional hazard regression analysis while adjusting for all demographic variables and covariates. Results: Significant results were obtained for acute conditions, such as ischemic heart disease and cerebral hemorrhage. The IRR of COVID-19- positive individuals compared with that of controls for the diagnosis of ischemic heart disease was 1.78 (1.57-2.02; 95% confidence interval [CI]) when adjusted for age and sex. HR was calculated as 3.02 (2.19-4.17; 95% CI) after adjusting for the covariates. In case of Cerebral hemorrhage, the adjusted IRR was 2.06 (1.25-3.40; 95% CI) and the adjusted HR was 4.08 (0.90-19.19; 95% CI). Conclusion: The findings of our study suggest that COVID-19 infection can be a significant risk factor for acute cardiovascular complications, such as ischemic heart disease and acute cerebrovascular complications, such as cerebral infarction, after properly adjusting for covariates.